DNA mimics of red fluorescent proteins (RFP) based on G-quadruplex-confined synthetic RFP chromophores. Issue 18 (13th September 2017) - Feng, Guangfu; Luo, Chao; Yi, Haibo; Yuan, Lin; Lin, Bin; Luo, Xingyu; Hu, Xiaoxiao; Wang, Honghui; Lei, Chunyang; Nie, Zhou; Yao, Shouzhuo
Abstract: Red fluorescent proteins (RFPs) have emerged as valuable biological markers for biomolecule imaging in living systems. Developing artificial fluorogenic systems that mimic RFPs remains an unmet challenge. Here, we describe the design and synthesis of six new chromophores analogous to the chromophores in RFPs. We demonstrate, for the first time, that encapsulating RFP chromophore analogues in canonical DNA G-quadruplexes (G4) can activate bright fluorescence spanning red and far-red spectral regions (Em = 583−668 nm) that nearly match the entire RFP palette. Theoretical calculations and molecular dynamics simulations reveal that DNA G4 greatly restricts radiationless deactivation of chromophores induced by a twisted intramolecular charge transfer (TICT). These DNA mimics of RFP exhibit attractive photophysical properties comparable or superior to natural RFPs, including high quantum yield, large Stokes shifts, excellent anti-photobleaching properties, and two-photon fluorescence. Moreover, these RFP chromophore analogues are a novel and distinctive type of topology-selective G4 probe specific to parallel G4 conformation. The DNA mimics of RFP have been further exploited for imaging of target proteins. Using cancer-specific cell membrane biomarkers as targets, long-term real-time monitoring in single live cell and two-photon fluorescence imaging in tissue sections have been achieved without the need for genetic coding.